Buenas prácticas de almacenamiento y conservación de la cadena de frío de vacunas durante el transporte hacia centros de atención primaria 2021 - Acuña Amaral, Cinthya (2023)
The present work allowed evaluating the level of compliance with the Good Storage Practices and the conservation of the cold chain of vaccines during transport to primary care centers in the Loreto Region. Exploratory study, with a non-experimental design, with a quantitative approach and because the data collection time was cross-sectional, the temperature recording was made by the data logger, downloaded via its own software and stored in the Excel program. The results show that the average temperature under controlled conditions (≤ 30 ºC) with a minimum load is optimal in thermos two (valid range from 2 to 8 ºC), the temperatures in thermos one and three being non-optimal; and, with a maximum load it is optimal in thermos two. The average of the temperature in the real transport route with a minimum load is optimal in all the thermos evaluated (T1, T2 and T3); while, with maximum load, it is optimal in thermoses two and three. The level of compliance with Good Storage Practices for the conservation of the cold chain of vaccines during transport to IPRESS I-4 Loreto Nauta and Hospital Santa Gema de Yurimaguas only occurred in thermos 2; with 91.30%, 100% and 95.65% for terms one to three respectively. It is concluded that only thermos 2 complies 100% with Good Storage Practices (operational and performance temperature with minimum and maximum load).